Redemptive children and historical memory: Luis mateo díez’s la gloria de los niños (2007) - Weng, Miaowei (Bulletin of Spanish Studies, 2020)
This article explores contemporary Spanish writer Luis Mateo Díez’s 2007 novel, La gloria de los niños, focusing on the construction of a redemptive child who mends the broken world and keeps alive historical memory. The author looks beyond one single nation state in his reconstruction of children and childhood under the Franco regime. Hidden behind his approach to the reconstruction of the ‘glorious children’ under Franco emerges, on the one hand, his dissolution of any authoritative version of Franco-era children and, on the other, his broader vision and desire to examine Spain and Spanish historical memory in a global context. © 2020 Bulletin of Spanish Studies.
Keywords: Childhood under Franco; Historical Memory; La gloria de los niños; Ladri di biciclette (1948); Luis Mateo Díez; Post Civil War period; Redemptive Child; Vittorio de Sica; Walter Benjamin; dept.wll; peer-reviewed

儿童与战争: 童年回忆和西班牙内战研究 = Children and the war - Weng, Miaowei (中国社会科学出版社, 2020)
本书将儿童,童年回忆和西班牙内战联系在一起,提出了"佛朗哥儿童"这个新概念.在童年研究和历史回忆研究的二元框架下,作者分析了"佛朗哥儿童"在西班牙20世纪后半叶至今的代表性文学影视作品,以此揭示出儿童在西班牙政治中的重要性,并呈现了西班牙近几十年来的历史和文化走向
Keywords: Wen xue yan jiu Xibanya; dept.wll

全球视野中的海外华人和中华文化 [Chinese Diasporas and Traditional Culture in the Global Context] - Weng, Miaowei (《中国与拉美》 [China and Latin America], 2022)
Keywords: dept.wll; peer-reviewed; ⛔ No DOI found